GAMBARAN PHARMACOVIGILANCE DAN HUBUNGAN FAKTOR YANG MEMPENGARUHI REAKSI OBAT YANG TIDAK DIINGINKAN (ROTD) PADA PASIEN PERESEPAN OBAT TUBERCULOSIS DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Abdur Rosyid; Farroh bintang sabiti; Destiara Firstie Roshani (Fakultas Farmasi Universitas Setia Budi, 2019)
Tuberculosis (TB) is still a growing global problem every year. TB disease is one of the 10 diseases that cause death worldwide (WHO, 2017). The design of this study is a qualitative observation with a prospective cross sectional design approach. The research was conducted at Sultan Agung Islamic Hospital, Semarang, from February to the desired sample size. From the subjects of tuberculosis patients with 92 patients. The number of patients experiencing ROTD with a dubious category was 56 patients (60.9%), in patients who experienced ROTD events with a possible category of 32 patients (34.8%), and in patients with ROTD with a category of probable 4 patients (4.3%). There is a significant relationship between age and ROTD incidence of a significance value of 0,000 and a significant relationship between sexes with ROTD incidence with a significance value of 0,000. Keyword : Therapy Tuberculosis, Adverse Drug Reactions